NILAI GIZI SNACK BAR TEPUNG CAMPURAN (TEPUNG MOCAF & TEPUNG KACANG MERAH) DAN SNACK BAR KOMERSIAL - Asriasih, Dwifa Novita; Purbowati; Anugrah, Riva Mustika (UNIVERSITAS NGUDI WALUYO, 2020)
Background: Snack bar is a snack in the form of a bar made from a mixture of various ingredients such as cereals, nuts. Mocaf flour and red bean flour are local food products that can be used as snack bar products. Objective: Find out an overview of the nutritional value of a mixed flour snack bar (mocaf &red bean flour) and a commercial snack bar.Research Method: Design of studyanalytic descriptive research. The research sample is a commercial snack bar. The types of commercial snack bars are obtained from supermarkets in Ungaran. Analysis of data using microsoft office excel and presented in table form. Results: Mixed flour snack bar (mocaf with red bean flour) contains 128 kcal of energy, 4.5 grams of protein, 3 grams of fat, 20.5 grams of carbohydrates, and 5.7 grams of fiber. The nutritional content of 11 commercial snack bar brands is 80-160 kcal energy, 1-6 gram protein, 2.5-10 gram fat, 10-19 gram carbohydrate, and 1-4 gram fiber. Conclusion: The nutritional content of the mixed flour snack bar (mocaf &red bean flour) contains higher fiber than the commercial snack bar. Abstrak : Latar Belakang :Snack bar merupakan makanan ringan yang berbentuk batangan berbahan dasar campuran dari berbagai bahan seperti sereal, kacang-kacangan. Tepung mocaf dan tepung kacang merah merupakan hasil pangan lokal yang dapat digunakan menjadi produk snack bar. Tujuan :Mengetahuigambaran nilai gizi snack bar tepung campuran (tepung mocaf & tepung kacang merah) dan snack bar komersial. Metode Penelitian :Desain penelitian deskriptif analitik. Sampel penelitian ini adalah snack bar komersial. Jenis-jenis snack bar komersial didapatkan dari swalayan yang ada di Ungaran. Analisis data menggunakan microsoft office excel dan disajikan dalam bentuk tabel. Hasil : Snack bar tepung campuran (tepung mocaf dengan tepung kacang merah) mengandung energi 128 kkal, protein 4,5 gram, lemak 3 gram, karbohidrat 20,5 gram, dan serat 5,7 gram. Kandungan gizi dari 11 merk snack bar komersial yaitu energi 80-160 kkal, protein 1-6 gram, lemak 2,5-10 gram, karbohidrat 10-19 gram, dan serat 1-4 gram. Simpulan :Kandungan gizi snack bar tepung campuran (tepung mocaf & tepung kacang merah) mengandung serat lebih tinggi daripada snack bar komersial.